2017
DOI: 10.1002/2016ja023498
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance dynamo effects over low‐latitude F region: A study by network of VHF spaced receivers

Abstract: Generation of equatorial spread F (ESF) irregularities resulting from magnetic disturbance is known for past few decades. However, better prediction models for this phenomenon are still lacking. Magnetic storms also affects the F region plasma drifts. In this work we examined variability in (i) occurrence of such freshly generated ESF and (ii) low‐latitude F region zonal plasma drifts over Indian longitude. For this purpose simultaneous observations of amplitude scintillations on 251 MHz signal, recorded by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…However, the scenario can be completely different if the DD electric field is modified by the presence of PP electric fields (N. Maruyama et al, ). It is shown that the effects in low‐latitude ionosphere in a given longitudinal sector can be different for nearly similar storms starting at different times (Kakad et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the scenario can be completely different if the DD electric field is modified by the presence of PP electric fields (N. Maruyama et al, ). It is shown that the effects in low‐latitude ionosphere in a given longitudinal sector can be different for nearly similar storms starting at different times (Kakad et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This enhanced heating modifies the neutral wind patterns in the high latitudes, which in turn sets up the disturbance dynamo (Blanc & Richmond, 1980). The effects of disturbance dynamo are globally observed in the Earth's atmosphere-ionosphere system (Fejer et al, 1991;Kakad et al, 2016;Kakad et al, 2017b). Even during quiet time the charged particles keep entering the high latitude polar region owing to open field configuration of the Earth's magnetic field lines.…”
Section: Data Sets and Energy Estimatesmentioning
confidence: 99%
“…On 28 March 2005, we noticed large enhancement (≈ 88.5 m/s) in the F region zonal plasma drifts as compared to their seasonal quiet time average of drifts 20 min prior to the start of the earthquake. This is an unusual observation because so far, even in the long‐term scintillation observations recorded at Tirunelveli, we have not observed such enhancement in zonal plasma drift on a magnetically quiet or disturbed day (Engavale et al, ; Kakad et al, ; ). It implies the presence of additional vertically downward electric field of approximately 3 mV/m, which is linked with the earthquake.…”
Section: Discussionmentioning
confidence: 57%
“…Day‐to‐day variation in the occurrence of ESF irregularities and their characteristics and ambient F region parameters like electron density, electric field, conductivities, and height are well reported in many earlier studies (Burke et al, ; Gurram et al, ; Kakad, Tiwari, & Pant, ; Li et al, ; Nishioka et al, ; Yamazaki et al, ). Apart from day‐to‐day variations, these parameters are also affected by the modulated neutral winds resulting from the enhanced Joule energies at high latitudes and prompt penetration electric fields during periods of geomagnetic storms (Bhattacharyya et al, ; Kakad et al, ; ; Kikuchi et al, ). Thus, in order to identify and quantify the effects associated with earthquakes in the equatorial F region, it is important to verify the level of geomagnetic activity on the earthquake days.…”
Section: Resultsmentioning
confidence: 99%